PERANAN RESPONSIBILITY ACCOUNTING DALAM COST CENTRE PADA PT. MARK DYNAMICS INDONESIA - Mulatua Silalahi; Dimita Purba (JURNAL MUTIARA AKUNTANSI, 2019)
Operating costs are an element of profit and loss calculation and hence the size of the operating costs will directly affect the income statement. The higher the profits obtained by using the amount of operating costs according to the budget shows that the use of business costs is more efficient, which means the performance of business costs is higher. PT. Mark Dynamics Indonesia is a company engaged in the field of passion fruit syrup. Based on the results of the study it can be concluded that the performance of business costs at PT. Mark Dynamics Indonesia in 2014 has decreased by a significant amount compared to 2013. The company has used a cost that is too large from the budget to obtain sales in the current period. From the analysis it is known that thus the company has not been able to streamline costs due to sales realization is smaller than the sales budget.